The Effect of Preoperative Magnetic Resonance Imaging on Long-term Oncological Outcomes Following Radical Prostatectomy—A 12-year Follow-up of a Randomized Controlled Trial - Daniyal Noor; Eduard Baco; Peter M. Lauritzen; Viktor Berge; Kristina F. Galtung; Maciej Jacewicz; Lars Magne Eri; Erik Rud (European Urology Open Science)
Background and objective: The effect of preoperative magnetic resonance imaging (MRI) on long-term oncological outcomes following robot-assisted laparoscopic prostatectomy (RALP) is uncertain. The objective was to investigate the effect of preoperative MRI on long-term oncological outcomes after RALP. Methods: A single-institution follow-up study of a randomized controlled trial was conducted, which included 438 patients with biopsy-confirmed prostate cancer scheduled for RALP between December 2009 and June 2012 (NCT06429878). No patients underwent MRI prior to biopsy. Patients were randomized into two groups: one without MRI (n = 216) and one with preoperative MRI (n = 222). The primary endpoints were disease-free (DFS) and overall (OS) survival. The effect of MRI on these endpoints was estimated using hazard ratios (HRs) with 95% confidence intervals (CIs). Key findings and limitations: The median age was 63 yr (interquartile range [IQR] 59–67), and the median prostate-specific antigen level was 7.9 ng/ml (IQR 5.9–11.4). Based on D’Amico risk classification, 112 patients were at a low risk, 220 at an intermediate risk, and 106 at a high risk. The median follow-up was 111 mo (95% CI: 104–118). The 12-yr DFS rate was 60% (95% CI: 54–65) and OS rate was 87% (95% CI: 84–90). Preoperative MRI did not improve DFS (HR 0.97, 95% CI: 0.71–1.34) or OS (HR 0.86, 95% CI: 0.52–1.40), with similar findings across clinical subgroups. Limitations include the following: oncological outcomes were secondary endpoints and MRI pathway has undergone changes since the trial. Conclusions and clinical implications: During a 12-yr follow-up after RALP, we did not observe a statistically significant difference in DFS or OS between patients who underwent preoperative MRI and those who did not. These findings highlight the need to assess the long-term impact of prebiopsy MRI. Patient summary: We studied whether having a magnetic resonance imaging (MRI) scan before prostate cancer surgery improves long-term outcomes. A total of 438 men with prostate cancer were included in this study and they were divided into two groups: one without MRI and one with MRI before surgery. The patients were followed for up to 12 yr, and we found no clear reduction in the risk of cancer recurrence or improved survival in patients who had undergone MRI. Today, MRI is performed routinely before biopsy, and more research is needed to evaluate whether this change has improved long-term outcomes.